Who am I? Who is she? : a naturalistic, holistic, somatic approach to personal identity - Montague, Gerard P. (Ontos Verlag, 2012)
Are 'persons' physical things, members of the species homo sapiens which exist solely in materialist form, continuous in structure with other living things? Or is the issue a more complex one: are there more dimensions to being a person than mere physical, biological existence? These are matters of interest and discussion in many fields of study in this age of individuality. In this wide-ranging essay, the author addresses various aspects of the issue, including the history of self and identity. The ancient tradition of dualism is rejected in favour of a straightforward holistic and naturalist.